The Level Of Teachers Understanding In Physical Education, Sports And Health About The 2013 Curriculum - Aprizal Fikri; Bayu Hardiyono (UNIB Press, 2020)
This study aims to determine the level of understanding of teachers in physical education, sports, and health in Line 20 Muara Padang District about K13 Learning. The research method used in this research is descriptive quantitative. The sample in this study were junior high schools in Line 20, Muara Padang district, Banyuasin district with a total of 20 teachers. This study uses 3 indicators, namely understanding the PJOK learning syllabus in the 2013 curriculum, understanding the principles of RPP preparation in learning PJOK in the 2013 curriculum, and understanding the methods of learning PJOK in the 2013 curriculum. The results showed that at the junior high school level understanding the PJOK learning syllabus in the curriculum 2013 got an average value of 54.2 of 55.% and was included in the high category.